School and Work in the Eastern Caribbean : Does the Education System Adequately Prepare Youth for the Global Economy? - Blom, Andreas (Washington, DC : World Bank, 2012)
This report comprises the first phase of analytical activities and focuses on the relevance of the education and training systems in the Organization of Eastern Caribbean States (OECS). Its findings confirm the importance of strengthening the link between OECS education and training systems and employers' needs. Analytical findings have also informed the design of a project in St. Lucia to pilot a new market-driven training model requiring close partnership between the public and private sectors. The second phase has already been discussed with the OECS governments and is in the preparation stage. It will develop innovative approaches to expand, diversify and finance nurse training programs to efficiently reduce local shortages within the context of a growing global demand and migration of trained nurses from the Caribbean. The third phase is expected to investigate the factors contributing to learning outcomes, particularly at the primary and secondary levels. The study will inform policies and actions that could lead to improved education quality, which Caribbean stakeholders have identified as fundamental to ensuring a more competitive regional workforce in the longer run. This report's analyses and conclusions confirm many views expressed by government officials, educators, youth, students, teachers, labor union members, private sector representatives, and development partners who participated in two events: (i) the St. Lucia Industry Roundtable for Skills for the Tourism Industry, in November 2005, and (ii) the Caribbean Lifelong Learning Forum in May 2006.1 The report also was reviewed both internally at the World Bank by leading experts in education and training, and externally by OECS stakeholders, including government officials, the Caribbean Examinations Council(CXC), and University of the West Indies.